Kompetensi Guru dalam Mengelola Kelas pada Pembelajaran Matematika Kelas V di Sekolah Penggerak SDN Cimayang 01 Pamijahan Bogor - Fitriani; hasanah, tita; Huda, Samsul (JURNAL KAJIAN ISLAM MODERN, 2024)
This research aims to determine teachers' skills in managing classes in mathematics learning in driving schools and analyzing supporting and inhibiting factors. The research method uses a qualitative approach with the type of field research. The research object consisted of key informants, namely the school principal and specialist informants, namely teachers and class V students at SDN Cimayang 01, Pamijahan District, Bogor Regency. Data collection techniques in this research used interviews, observation and documentation. Data analysis was carried out using triangulation. The results of the research show that teachers at SDN Cimayang 01 already understand the techniques for managing the class, this can be seen from the teacher's skills in conditioning the class, responsiveness, giving even attention, skilled at providing instructions and goals, skilled at giving reprimands, and skilled at providing reinforcement. The teacher's skills are also a supporting factor for the teacher's success in managing the class. Meanwhile, the obstacles for teachers in managing classes in mathematics are the curriculum system which is always changing, the limitations of teachers in mastering learning using the Independent Curriculum, factors from the students themselves, as well as the availability of facilities and infrastructure owned by the school.